A new canopy-dwelling species of the genus Alloscopus Börner (Collembola: Orchesellidae: Heteromurinae) from Mt. Makiling, Philippines - Alviola, Marnelli S.; Lucañas, Cristian C.; Jr., Ireneo L. Lit; Soto-Adames, Felipe N.; Jantarit, Sopark (Zootaxa, 2024)
A new species of Alloscopus Börner, 1906 (Orchesellidae: Heteromurinae), A. arborealis sp. nov., is herein described from Mt. Makiling, Laguna, Philippines. The new species is distinct from its blind congeners by the combination of: 7+7 macrochaetae on head ‘An’ series and 1+1 on ‘M’ series; 13+13 macrochaetae on thorax II (vs. 9–12) and 7+7 central on thorax III (vs. 6+6); absence of the microsensilla on abdomen I; abdomen IV with four sensilla (vs. three); and ventral tube with a small number of chaetae on its posterior face (4–5 vs. 11–23) and lateral flap (7 vs. 9–16). The complete body chaetotaxic pattern of the new species and a revised key to the world fauna of Alloscopus are also provided.